'[T]hen along comes Mr Carnegie': Carnegie travel fellowships and the professional development of kindergarteners in 1930s New Zealand. Issue 2 (3rd April 2018) - Bethell, Kerry
Abstract: This article chronicles the experiences of four New Zealand kindergarten teachers who, between 1932 and 1937, were individually awarded Carnegie Corporation of New York Travel Fellowships to undertake an academic year of advanced study at the progressive Teachers College at Columbia University in New York and to visit educational provisions in parts of America and, on their way home, in Britain. Why and how these teachers were selected for fellowship grants is explored within the context of two parallel stories. One concerns the efforts of the Carnegie Corporation of New York and the Teachers College, Columbia University to promote international trends in professional training and practice and the other, the work of the New Zealand Free Kindergarten Union to utilise professional networks, both nationally and internationally, to enhance the professional training of kindergarten teachers. On their return home, the fellowship holders sought to implement their new understandings of progressive models of learning in their work with young children, parents and teachers, contributing grass-roots efforts to the transnational spread of progressive thought and practice over the first decades of the twentieth century.